2010
DOI: 10.1016/j.scriptamat.2010.04.041
|View full text |Cite
|
Sign up to set email alerts
|

A large thermoelectric figure of merit of La-doped SrTiO3 prepared by combustion synthesis with post-spark plasma sintering

Abstract: We investigated figure of merit in La-doped SrTiO 3 prepared by Combustion Synthesis (CS) with post Spark Plasma Sintering (SPS), on which effect of sintering time was mainly examined. The samples of Sr 0.92 La 0.08 TiO 3, CSed from oxides, carbonate, metal and sodium perchlorate, was prepared by SPS at 1573 K for 1, 5, 15 and 30 min for measuring thermoelectric properties from RT to 1173K. In conclusion, only 5-min-sintered product recorded a maximum value of 0.37 in figure of merit at 1045 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 27 publications
(29 reference statements)
2
46
0
3
Order By: Relevance
“…The relative densities of all samples are higher than 95%, comparable to those of samples prepared by SPS. 10 The temperature dependence of the electrical resistivity (q) of the Sr 1Àx Dy x TiO 3 ceramics is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative densities of all samples are higher than 95%, comparable to those of samples prepared by SPS. 10 The temperature dependence of the electrical resistivity (q) of the Sr 1Àx Dy x TiO 3 ceramics is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…SrTiO 3 is one of the most important candidate n-type thermoelectric oxides, 1,2 and many researchers have studied the thermoelectric properties of SrTiO 3 -based materials. [3][4][5][6][7] There have been many investigations into fabrication methods for SrTiO 3 ceramics, for example, the hydrothermal method, 8 the sol-gel method, 9 combustion synthesis combined with spark plasma sintering (SPS), 10 and the solid-state reaction method (SSR). 11 In our previous studies, it was found that performing the solid-state reaction method in an oxygen-reduced atmosphere (reduced SSR method) could significantly improve the thermoelectric performance of SrTiO 3 -based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional SSR and the sol-gel method are simple techniques in many types of synthesis methods for oxide thermoelectric materials. Many other methods, such as hydrothermal, 67 combustion, 68 sol-gel, 66 etc, are available, but we do not discuss them in detail. For the SrTiO 3 -based materials, we list only the highest figure of merit obtained using each synthesis method in Figure 6.16.…”
Section: Sol-gel and Spsmentioning
confidence: 99%
“…For simplicity, only a pair of n-type and p-type elements are presented in the figure, 1 but a real device for 16 Figure of merit for the SrTiO 3 system produced by different methods.HT: hydrothermal; SSR: conventional solid-state reaction technology; CS þ SPS: combustion synthesis and SPS; SG þ SPS: sol-gel and SPS [65][66][67][68]. …”
mentioning
confidence: 99%
“…Excellent agreement between transport properties deduced from SE and direct electrical measurements suggests that SE is an effective tool for studying oxide thin film thermoelectrics. [10][11][12][13] Owing to its structural and chemical stability at high temperatures 9 and a high electron effective mass, 14 electron doped STO thin films are considered as excellent candidates for high temperature thermoelectric applications. 3,15,16 For accurate description of Seebeck coefficient of thin films, the effective mass of carriers and scattering parameter need to be determined together with the transport properties such as electrical conductivity, carrier concentration, and mobility.…”
mentioning
confidence: 99%